Scaling‐up: Building, Leading and Sustaining Rapid Growth Over Time - Jansen, Justin J. P.; Heavey, Ciaran; Mom, Tom J. M.; Simsek, Zeki; Zahra, Shaker A. (Journal of Management Studies, 2023)
AbstractEven as research on scaling and high growth firms (HFGs) is gaining momentum, the corpus of accumulated research remains largely fragmented and dispersed, with little in the way of a central conceptual foundation or ‘theoretical true north’ to guide empirical development. This Special Issue provides a forum for works that push the theoretical and empirical frontiers of research on scaling and HGFs. We provide a multi‐dimensional conceptualization that recognizes scaling as a dynamic capability entailing routines and processes for expansion, replication, and synchronization. We also present a typology that specifies the multiple types of HGFs. Inspired by the four studies published in the special issue, we finally outline five priorities for future research.